Analysis of phi and chi 1 torsion angles for hen lysozyme in solution from 1H NMR spin-spin coupling constants. - Smith, L; Sutcliffe, M; Redfield, C; Dobson, C (1991)
Three-bond 3JHN alpha coupling constants have been determined for 106 residues and 3J alpha beta coupling constants have been measured for 57 residues of the 129-residue protein hen egg white lysozyme. These NMR data have been compared with torsion angles defined in the tetragonal and the triclinic crystal forms of the protein. For most residues the measured 3JHN alpha values were consistent with the phi torsion angles found in both crystal forms; the RMS difference between the coupling constants calculated by using the tetragonal crystal structure phi angles and the experimental 3JHN alpha values is 0.88 Hz. Thus there appears to be no significant averaging of the phi torsion angle either in the interior or at the surface of the protein. For 41 of the residues where 3J alpha beta coupling constants have been determined, the values are consistent with a single staggered conformation about the chi 1 torsion angle and there is complete agreement between the NMR data in solution and the torsion angles defined in the crystalline state. In contrast, for the other 16 residues where 3J alpha beta coupling constant values have been measured, the data indicate extensive motional averaging about the chi 1 torsion angle. These residues occur largely on the surface of the protein and examination of the crystal structures shows that many of these residues adopt a different conformation in the triclinic and tetragonal crystal forms and have high crystallographic temperature factors. It appears, however, that in solution conformational flexibility of the side chains of surface residues is significantly more pronounced than in individual crystal structures.